Assessment of cancer related fatigue - R. Strebkova; M. Petkova; M. Minev (Trakia Journal of Sciences)
Cancer-related fatigue is one of the most common and significant symptoms experienced by cancer patients. The cancer-related fatigue can occur at any stage of the disease or its treatment and has an impact on patient's quality of life, regarding physical functioning and the ability to perform activities of daily living. In addition, it is associated with psychological distress. There is no agreement between various authors about the definition and measurement of cancer-related fatigue. There is a range of scales which measure cancer-related fatigue based on unidimensional or multi-dimensional perspective. This review aims to identify available tools applied in practice for the measurement and evaluation of cancer-related fatigue and discusses important conceptual and psychometric characteristics of these instruments.